2011
DOI: 10.1371/journal.pone.0023646
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Intervention Studies with Telmisartan, Ramipril and Their Combination in Different Rat Stroke Models

Abstract: ObjectivesThe effects of AT1 receptor blocker, telmisartan, and the ACE inhibitor, ramipril, were tested head-to head and in combination on stroke prevention in hypertensive rats and on potential neuroprotection in acute cerebral ischemia in normotensive rats.Methods Prevention study: Stroke-prone spontaneously hypertensive rats (SHR-SP) were subjected to high salt and randomly assigned to 4 groups: (1) untreated (NaCl, n = 24), (2) telmisartan (T; n = 27), (3) ramipril (R; n = 27) and (4) telmisartan +ramipri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 33 publications
3
19
0
1
Order By: Relevance
“…SHRSPs develop severe hypertension with age and die from ischemic stroke or hemorrhagic stroke in greater than 80% of the animals [47]. Telmisartan reduces the incidence of stroke, prolongs survival, and improves neurological outcome in SHRSPs [49]. Irbesartan also increases the survival rate in SHRSPs fed a high-salt and low-protein diet, and ameliorates the appearance of stroke symptoms, showing an association with the prevention of microscopic lesions [50].…”
Section: Experimental Studies Of Arbsmentioning
confidence: 99%
See 1 more Smart Citation
“…SHRSPs develop severe hypertension with age and die from ischemic stroke or hemorrhagic stroke in greater than 80% of the animals [47]. Telmisartan reduces the incidence of stroke, prolongs survival, and improves neurological outcome in SHRSPs [49]. Irbesartan also increases the survival rate in SHRSPs fed a high-salt and low-protein diet, and ameliorates the appearance of stroke symptoms, showing an association with the prevention of microscopic lesions [50].…”
Section: Experimental Studies Of Arbsmentioning
confidence: 99%
“…BDNF acts on certain neurons of the central and peripheral nervous systems to support the survival of existing neurons, and encourage the growth and differentiation of new neurons and synapses [53,54]. Telmisartan improves neurological outcome, reduces infarct size and TNF-α levels, and induces expression of the TrkB receptor and neuronal survival in a rat MCAO model [49]. Irbesartan also improves neurological outcome, reduces infarct size, decreases the number of apoptotic cells in the peri-infarct cortex, and attenuates the invasion of activated microglia and macrophages in the peri-infarct cortex in the rat MCAO model [55].…”
Section: Experimental Studies Of Arbsmentioning
confidence: 99%
“…Doses were selected on the basis of previous studies in the laboratory and those reported in the literature. [20][21][22][23] The animals were selected randomly based on their body weight into nine groups and each group comprised six animals. The study was performed in multiple phases as shown in the experimental protocol (Scheme 1).…”
Section: Drugs and Treatment Schedulementioning
confidence: 99%
“…Deguchi et al demonstrated that TMS dose-dependently (0.3 mg/kg/day or 3 mg/kg/day) ameliorated metabolic syndrome related changes in the post stroke brain of SR-SHR with direct neuroprotective effects [34]. Moreover, incidence of stroke was reduced along with prolonged survival and improved neurological outcome following TMS application (0.5 mg/kg once daily) [35]. Pretreatment of rats with TMS (1 mg/kg) seven days before inducing cerebral ischemia also showed significant reduced infarct size and histopathologically normal appearance of neurons in the periinfarct cortical regions [36].…”
Section: Preclinical Studies On Sartans In Animal Models Of Ischemic mentioning
confidence: 99%